THE ROLE OF SYMBOLS IN TARAS SHEVCHENKO’S TEXT STRUCTURE OF “ZHURNAL” - Ільків, А. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article investigates the compositional role of symbols in T. Shevchenko’s diary. The symbolism of dreams is analyzed and their ingenuous connection with reality is revealed. Functions of dreams and their role in creation the plot of the diary are defined.